Birth Preparedness and Complication Readiness Practices Among Pregnant Adolescents in Bangkok, Thailand - Teekhasaenee, Tiradech (Adolesc Health Med Ther, 2020)
BACKGROUND: Reducing the maternal mortality ratio is one of the United Nations Sustainable Development Goals. These maternal deaths are preventable with appropriate management and care. Birth preparedness and complication readiness (BPCR) is a strategy to make prompt decisions to seek care from skilled birth attendants, resulting in reduced maternal and neonatal mortality. Despite high global rates of adolescent pregnancy, there has not yet been a study of BPCR status and associated factors among pregnant adolescents. OBJECTIVE: To assess the proportion of, and associated factors for, good BPCR in adolescent pregnant women attending antenatal clinic in an urban tertiary care hospital. MATERIALS AND METHODS: This cross-sectional survey was conducted among adolescent pregnant women attending antenatal clinic at the Department of Obstetrics and Gynecology, Faculty of Medicine Vajira Hospital, Thailand, from September 1st, 2018 to March 31st, 2019. A total of 134 adolescent pregnant women were recruited. The participants and their parents or legal guardians were informed of the study process at the antenatal clinic before their parents or legal guardians, granted written consent on their behalf. The participants were interviewed using the BPCR index, which was adapted from the John Hopkins Program for International Education in Gynecology and Obstetrics. RESULTS: The proportion of good BPCR in adolescent pregnant women in an urban tertiary care hospital was 78.4%. The most mentioned aspect of BPCR was planning to give birth with a skilled provider (92.5%). The significant associated factor for good BPCR was the number of ANC ≥ 4 (odds ratio 3.2, 95% CI 1.13–9.05, p=0.023). CONCLUSION: This study demonstrated that the proportion of good BPCR among adolescent pregnant women attending an urban tertiary care hospital was high. The associated factor of good BPCR was the number of ANC ≥ 4.